2015
DOI: 10.1002/jccs.201500257
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Tetrazole Derivatives of Spiro‐ and Bis‐barbiturates

Abstract: This work described the synthesis of the first and unprecedented examples of 5-aryl-1H-tetrazoles including spiro-and bis-(thio)barbiturates, generated from the reaction between 4-(1H-tetrazol-5-yl)benzaldehyde with (thio)barbituric acids and cyanogen bromide (BrCN) in the presence of triethylamine, providing good overall yields. Tetrazoles based on bis-(thio) barbiturates were also obtained in the absence of BrCN under the same conditions. The structures were characterized by IR, 1 H NMR, 13 C NMR, X-ray crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In 2015, Noroozi Pesyan et al reported that the reaction of 4‐cyanobenzaldehyde with sodium azide in the presence of catalytic amounts of montmorillonite K10 in refluxing DMF for 24 h gave 4‐(1 H ‐tetrazol‐5‐yl)benzaldehyde (127) and then its reaction with BrCN and some (thio)barbiturates 4 in CH 3 OH resulted 5‐substituted tetrazoles including spiro barbiturates 128 in 60%–80% yields in the presence of triethylamine and/or L‐(+)‐TA as a basic and acidic conditions, respectively (Scheme 45, paths a and b ) [63].…”
Section: Synthesis Of Spiro[furo[23‐d]‐pyrimidinesmentioning
confidence: 99%
“…In 2015, Noroozi Pesyan et al reported that the reaction of 4‐cyanobenzaldehyde with sodium azide in the presence of catalytic amounts of montmorillonite K10 in refluxing DMF for 24 h gave 4‐(1 H ‐tetrazol‐5‐yl)benzaldehyde (127) and then its reaction with BrCN and some (thio)barbiturates 4 in CH 3 OH resulted 5‐substituted tetrazoles including spiro barbiturates 128 in 60%–80% yields in the presence of triethylamine and/or L‐(+)‐TA as a basic and acidic conditions, respectively (Scheme 45, paths a and b ) [63].…”
Section: Synthesis Of Spiro[furo[23‐d]‐pyrimidinesmentioning
confidence: 99%
“…[ 15 ] One‐pot reaction of (thio)barbituric acids with aldehydes and cyanogen bromide yield spiro furo[2,3‐ d ] pyrimidines. [ 16–21 ]…”
Section: Introductionmentioning
confidence: 99%